The relationship between the use of the Unidroit Principles and the CISG in a comparative view and how the Unidroit Principles contribute to the interpretation of the CISG - Starzmann, Katrin (Department of Commercial Law, 2014)
The content and scope of the thesis is to demonstrate and elaborate the coherence between the Unidroit Principles and the CISG. Further the focus will be on the dif-ferences in power and impact of the Unidroit Principles and the CISG as well as the differences in regulating certain issues. Attention is drawn to specific regulations and their content and scope will be compared in order to determine the influence and help of the Unidroit Principles to interpret the CISG and answer the question if the two sets of provisions can be seen as alternatives or complementary instruments.